B cells in the pneumococcus-infected lung are heterogeneous and require CD4+ T cell help including CD40L to become resident memory B cells - Etesami, Neelou S.; Barker, Kimberly A.; Shenoy, Anukul T.; De Ana, Carolina Lyon; Arafa, Emad I.; Grifno, Gabrielle N.; Matschulat, Adeline M.; Vannini, Michael E.; Pihl, Riley M. F.; Breen, Michael P.; Soucy, Alicia M.; Goltry, Wesley N.; et al. (Frontiers in Immunology, 2024)
Recovery from respiratory pneumococcal infections generates lung-localized protection against heterotypic bacteria, mediated by resident memory lymphocytes. Optimal protection in mice requires re-exposure to pneumococcus within days of initial infection. We found that this stimulates the immediate accumulation of dynamic and heterogeneous populations of B cells in the lung, and is essential for the establishment of lung resident memory B (BRM) cells. The B cells in this early wave were activated, proliferating locally, and associated with both CD4 + T cells and CXCL13. During this early timeframe, lymphocyte recirculation, CD4 + cells, and CD40 ligand (CD40L) signaling were all needed for lung BRM cell establishment, whereas CXCL13 signaling was not. While most prominent as aggregates in the loose connective tissue of bronchovascular bundles, lung BRM cells were equally numerous as single cells dispersed throughout the alveolar septae. We propose that CD40L signaling from antigen-stimulated CD4 + T cells in the infected lung is critical to establishment of local BRM cells, which subsequently protect the airways and parenchyma against future potential infections.